Respuesta :

Answer:

14) [tex]f(10) = 10[/tex], 15) [tex]f(-2) = -2[/tex], 16) [tex]f(a) = a[/tex], 17) [tex]f(a+b) = a+b[/tex], 18) [tex]g(10) = 38[/tex], 19) [tex]g(-2) = -22[/tex], 20) [tex]g(a) = 5\cdot a - 12[/tex], 21) [tex]g(a+b) = 5\cdot a +5\cdot b -12[/tex]

Step-by-step explanation:

Let [tex]f(x) = x[/tex] and [tex]g(x) = 5\cdot x - 12[/tex], we proceed to resolve on each case:

14) [tex]f(10)[/tex]

[tex]f(x) = x[/tex]

[tex]f(10) = 10[/tex]

15) [tex]f(-2)[/tex]

[tex]f(x) = x[/tex]

[tex]f(-2) = -2[/tex]

16) [tex]f(a)[/tex]

[tex]f(x) = x[/tex]

[tex]f(a) = a[/tex]

17) [tex]f(a+b)[/tex]

[tex]f(x) = x[/tex]

[tex]f(a+b) = a+b[/tex]

18) [tex]g(10)[/tex]

[tex]g(x) = 5\cdot x - 12[/tex]

[tex]g(10) = 5\cdot (10) -12[/tex]

[tex]g(10) = 38[/tex]

19) [tex]g(-2)[/tex]

[tex]g(x) = 5\cdot x - 12[/tex]

[tex]g(-2) = 5\cdot (-2) -12[/tex]

[tex]g(-2) = -22[/tex]

20) [tex]g(a)[/tex]

[tex]g(x) = 5\cdot x - 12[/tex]

[tex]g(a) = 5\cdot a - 12[/tex]

21) [tex]g(a+b)[/tex]

[tex]g(x) = 5\cdot x - 12[/tex]

[tex]g(a+b) = 5\cdot (a+b) -12[/tex]

[tex]g(a+b) = 5\cdot a +5\cdot b -12[/tex]

ACCESS MORE